Force generation in sprint running is related to muscle properties in male sprinters - Monte, A.; Zamparo, P. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to investigate the relationship between muscle properties (MP) and force production (F) during a sprint running acceleration phase in 18 male sprinters (Age: 24.4±4 years; personal best: 10.66±0.5 s). MP (muscle thickness, fascicle length and pennation angle) of the lower limb muscles were measured by B-mode ultrasonography and F was modelled at each instant by derivation of running velocity. All MP variables showed significant correlations with peak force values (p>0.01): longer fascicle length, greater thickness and lower pennation angle are associated with greater force production and subsequent acceleration ability.